2018
DOI: 10.4155/bio-2018-0110
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive and Selective LC–MS/MS Method for Quantitation of Ivermectin in Human, Mouse and Monkey Plasma: Clinical Validation

Abstract: A sensitive and selective LC-MS/MS method was validated for quantitation of ivermectin (IVM) in plasma. Method: The IVM was extracted from plasma using solid-phase extraction with C-18 cartridges. Separation of analytes was achieved on an ACE C18 column with isocratic elution using 0.1% acetic acid and methanol: acetonitrile (1:1, v/v) as mobile phase. The IVM was quantitated using electrospray ionization operating in negative multiple reaction monitoring mode. Results: The MS/MS response was linear over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The plasma samples were collected before dosing and at 1, 2, 3, 4, 6, 8, 12, 24, 48, and 72 hours. Plasma samples were analyzed using the previously described validated liquid chromatography-mass spectrometric (LC-MS/MS) methods [ 19 21 ]. A visual predictive check with 1,000 replicates was performed after fixing structural and error parameters estimated by the final model.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma samples were collected before dosing and at 1, 2, 3, 4, 6, 8, 12, 24, 48, and 72 hours. Plasma samples were analyzed using the previously described validated liquid chromatography-mass spectrometric (LC-MS/MS) methods [ 19 21 ]. A visual predictive check with 1,000 replicates was performed after fixing structural and error parameters estimated by the final model.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of 0.1% AA to both the aqueous and organic phase (acetonitrile) resulted in a better signal for DORA, compared to water and 0.1% FA, whereas for IVER the best results were obtained by using no organic modifier (see Figure S1A). MOXI was not tested during the initial experiment, but Chhonker et al 2018 [24] also previously reported 0.1%AA as an organic modifier for MOXI. By reducing the AA concentration from 0.1% to 0.01%, the signal intensity for IVER and MOXI increased, whereas a decreased signal intensity for DORA was observed (see Figure S1B).…”
Section: Internal Standardizationmentioning
confidence: 99%
“…LC-MS/MS also allows accurate simultaneous analysis of mixtures in biological matrices, such as plasma. A few studies have been reported for quantification of MLs using LC-MS/MS methods in biological matrices, such as in milk [20], lamb tissues [21,22], and lamb serum [23], human [24], dog [25], and calf [26] plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Iglesias et al used the same method for soil and cattle feces [13]. Liquid chromatography-tandem mass spectrometry (LC-MS-MS) has also been shown in several studies to be useful for multiple matrixes such as plasma, milk, liver, and whole blood [14][15][16][17][18][19][20]. Liquid chromatography-electrospray ionization-mass spectrometry/mass spectrometry (LC-ESI-MS/MS) has also been used to detect macrocyclic lactones in fsh muscle [14].…”
Section: Introductionmentioning
confidence: 99%